Comportamiento de conejos alimentados con plantas forrajeras tropicales en la Finca Experimental La María de la Universidad Técnica Estatal De Quevedo. - Tubay Chóez, Tulio Cesáreo (2015)
The investigations were carried out in belonging to the State Technical University of Quevedo (UTEQ) Experimental farm "La Maria" of the Faculty of Animal Science (FCP), located on the road to Mocache, km 7 1/2 via Quevedo -The Empalme Region Quevedo, province of Los Rios, Ecuador, to 01º 06 '028' south latitude and 70 ° 27 '13 "W and a height of 72 meters. In research 1, the productive response in New Zealand rabbits fed cockade (T1), mulberry (T2), tropical kudzu (T3) and a control (: balanced T4) was evaluated. In research 2 different levels of consumption of mulberry (T2 100, T3: T4 200 and 300 g), replacing the commercial feed (T1). And a control treatment (T1): While research 3, the response to the consumption of hydroponic forage of mulberry (FVHM) in three periods wilt (: 24 and T4 36 hours T3 12 T2) was determined. A completely randomized design (CRD) with five repetitions was applied. The size of the experimental unit consisted of two animals. In each of the investigations 30 New Zealand rabbits aged 30 days were used, with an average weight of 450 g. Feed intake (CA), weight gain (GP), feed conversion ratio (ICA), carcass weight (PC) and performance to the (RC) channel was evaluated. The greatest CA (P <0.05) in research 1; 2 and 3 the treatments T3 recorded; T1 and T1 (139.08, 160.07 and 96.21 g DM animal-1 day-1). The GP; ICA; PC more efficient and RC (P <0.05) in research 1, the reported treatment T2 (27.27 g animal-1 day-1, 3.40; 1267 54.40 % 50 g, respectively). The revised data show that there is interesting nutritional potential in tropical forages profitable feeding rabbits and to promote production methods that allow the best use of available resources, consistent with local conditions of small and medium producers. Keywords: Food, nutrition, forage, shrubs, rabbits